Motor Flex : Análise comparativa de performance e emissão de gases com diferentes combustíveis - Viana, Lívio Bruno Nery da Silva (2023)
This work studies the phenomenon of minimizing pollutants, with an impact on environmental preservation and the reduction of greenhouse gas emissions, seeking to comply with the Air Pollution Control Program for Motor Vehicles (PROCONVE) L7 and L8, where it is necessary to, by 2030, reduce the use of fossil fuels, thus preserving the environment as well as seeking a possible cost reduction, by using a less harmful and cheaper fuel when using internal combustion engines. Its objectives are to analyze the mechanical performance of a 4-cylinder Renault D4D engine, using Hydrated Ethanol (concentration 96% w/w) and gasoline, and thus validate the data experimentally, and, in this way, obtain multidimensional data on gaseous emissions. arising from the combustion of these elements with an emphasis on NOx, CO and HC. In relation to the materials and methods used, the use of the KIVA 3Vr-2 software can be highlighted, which was responsible for simulating, in real conditions, internal combustion engines, parameters in the air-fuel mixture, internal temperature, chemical kinetics and turbulence, finally presenting the results that were compared. The simulations were carried out using hydrated ethanol and gasoline. It can be concluded that the use of ethanol is advantageous compared to the use of gasoline, because from the performance point of view, the engine was able to maintain its operability characteristics. However, from the emissions point of view, it was observed that ethanol is more cost-effective, as it emits around five times less CO than gasoline, however, attention should be paid to the NOx emission values of ethanol, which were higher than those of gasoline.